(untitled) (American AgriTech: Journal of Agricultural Technology Innovation and Sustainability, 2026)
The experiments were conducted on 45 30-day-old rabbits of the local breed. 3 groups were formed for the experiment. Group 1 rabbits were the control group and were fed with mixed feed used on the farm until the end of the experiment. Groups 2-3 were the experimental group rabbits, which were given different amounts of Permasol - 500 mineral with their diet from day 30 to day 70 for 40 days. In particular: rabbits of the 2nd experimental group were given 6g/kg, and rabbits of the 3rd experimental group were given 10g/kg. At the end of the experiment, the best results were observed in rabbits of the second experimental group. In particular, compared to their peers in the control group, erythrocytes were 19.53%, hemoglobin 10.08%, leukocytes 8.06%, total protein 13.55%, albumin 10.70%, calcium 9.73%, phosphorus 23.91%, AST 27.17%, ALT 12.94%. Natural resistance was also found to be higher in group 2 rabbits.